2016
DOI: 10.1371/journal.pone.0164036
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Class II Bacteriocins to Modify Gut Microbiota to Improve Host Health

Abstract: Production of bacteriocins is a potential probiotic feature of many lactic acid bacteria (LAB) as it can help prevent the growth of pathogens in gut environments. However, knowledge on bacteriocin producers in situ and their function in the gut of healthy animals is still limited. In this study, we investigated five bacteriocin-producing strains of LAB and their isogenic non-producing mutants for probiotic values. The LAB bacteriocins, sakacin A (SakA), pediocin PA-1 (PedPA-1), enterocins P, Q and L50 (enteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 72 publications
1
85
0
Order By: Relevance
“…The bacteriocins are produced by food- or gut-associated LAB and belong to different subclasses of class II bacteriocins: sakacin A (class IIa), pediocin PA-1 (class IIa), enterocins P, Q and L50 (class IIb and IId), plantaricins EF and JK (class IIb) and garvicin ML (class IIc) [94]. When analysing the microbial community in faeces, it was observed that the overall structure remained largely unaffected in different treatments.…”
Section: Bacteriocinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacteriocins are produced by food- or gut-associated LAB and belong to different subclasses of class II bacteriocins: sakacin A (class IIa), pediocin PA-1 (class IIa), enterocins P, Q and L50 (class IIb and IId), plantaricins EF and JK (class IIb) and garvicin ML (class IIc) [94]. When analysing the microbial community in faeces, it was observed that the overall structure remained largely unaffected in different treatments.…”
Section: Bacteriocinsmentioning
confidence: 99%
“… a   Observations in the presence of bacteriocin-producing strains only; b  observations in the presence of both bacteriocin-producing and non-bacteriocin-producing strains.LAB, lactic acid bacteria.Adapted from [94]. …”
Section: Bacteriocinsmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the metabolic potential of each genome, we found evidence that the extent of prematurity, either directly or indirectly, can affect the gut microbiome. Given evidence that a lower gestational age may limit bacteriocin and vitamin production, which are factors that can impact community structure and lead to inflammation 30,31 , these findings may inform our understanding of diseases associated with dysbiosis of the microbiome, especially in very premature infants.…”
Section: Discussionmentioning
confidence: 95%
“…A true inhibition zone is depicted in Figure 2(c), where the toxin strength has been increased past κ * ; here x R has again been set to its maximum, and therefore x 0 takes its minimum value, i.e. the size of the inhibition zone (29).…”
Section: A Two-colony Solution With Immotile Bacteriamentioning
confidence: 99%